Hohenbuehelia filicina sp. nov. (Agaricales, Basidiomycota), from Southwestern Siberia, Russia - Kalinina, Lyudmila B.; Ageev, Dmitry V.; Bulyonkova, Tatiana M. (Phytotaxa, 2023)
Hohenbuehelia filicina, a new species from Southwestern Siberia, Russia is described. It is morphologically, ecologically and phylogenetically well differentiated from the other species of the genus. The unique combination of morphology (relatively long stipe, white fruitbodies) and substrate preference (growing exclusively on live ostrich ferns) make the species easily recognizable even in the field. Phylogenetic analysis was performed to confirm the identity of new species.